The influence of work discipline on Employee performance (case study at PT. Herlinah Cipta Pratama) - Paroli Paroli; Nabila Halfa Rifani (Jurnal Mantik, 2023)
This research is motivated by the performance of PT employees. Herlinah Cipta Pratama is not yet optimal, one of the factors is the lack of application of work discipline. Some employees do not comply with company rules and ignore them. Awareness of the importance of implementing work discipline in companies is also lacking, and this can have a negative impact on employee performance. The aim of this research is to find out whether there is an influence between work discipline and employee performance at PT. Herlinah Cipta Pratama. This research uses quantitative methods with descriptive and causal associative approaches. The research results show that work discipline has a positive influence on employee performance at PT. Herlinah Cipta Pratama. This means that the higher the level of work discipline applied by employees, the better their performance in the company. These results can be the basis for the company PT. Herlinah Cipta Pratama in developing policies and programs that can improve employee work discipline, with the aim of improving their overall performance